Newest Updates in Rheumatology - Wahid Ali Khan (IntechOpen, 2018)
This book is a comprehensive guide to rheumatology and includes all possible topics. The book is ideal for all those interested in the field of rheumatology, including students, scientists, and postdocs.
English
Keywords: Medicine; Immunology; Allergology and Rheumatology; Health Sciences